The role of Adlai Stevenson in the settlement of the Cuban missile crisis of 1962 - Пасічник, Н. (Київський національний університет імені Тараса Шевченка, 2013)
The influence of Permanent Representative to the United Nations Adlai Stevenson on the settlement of the Cuban missile crisis of 1962 is analysed.

Аналізується вплив постійного представника США в ООН Е. Стівенсона на врегулювання Кубинської ракетної кризи 1962 р.
Роль Е. Стівенсона у врегулюванні Кубинської ракетної кризи 1962 р.
Keywords: USA; UN; Cuban missile crisis; A. Stevenson; США; ООН; Кубинська ракетна криза; Е. Стівенсон